Clinical results and life quality of patients with cervical cancer at a combined immunotherapy - D. K. Kenbayeva; A. F. Lazarev; Z. A. Manambayeva (Опухоли женской репродуктивной системы, 2014)
In the publication some clinical results and characteristics of dynamics of life quality in patients with cervical cancer are presented at carrying out an immunotherapy. Complex inspection of 77 patients, including 40 – with IIB and 37 – with the III clinical stage is carried out. The increase in extent of primary tumor regression is revealed at a combination of beam the